2020
DOI: 10.5267/j.msl.2019.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Deposit insurance fund and the quality of risk assets of Nigerian deposit money banks

Abstract: This paper empirically assesses the relationship between Deposit Insurance Funds (DIF) and the quality of risk assets of listed Deposit Money Banks (DMBs) in Nigeria. The entire fifteen listed DMBs in the country as of 31st December, 2017 were focused on and the secondary data were subsequently sourced from the yearly financials of the Nigeria Deposit Insurance Corporation (NDIC) for a 29-year period covering from 1989 to 2017. The Auto-Regressive Distributed Lag (ARDL) and the Vector Error Correction (VEC) es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The impact of the growth of deposits onto the Deposit Insurance System's funds and its pay out capacity are as follows -the payout capacity is always larger at lower covered deposits' annual growth rate. Authorities should take into account the growth of deposits' impact when deciding on an annual premium level, especially if the country experienced a significant growth of deposits (Ognjenović, 2017, p. 123) Empirical research conducted in order to assess the relationship between the Deposit Insurance Fund and total deposits and loans showed that the volume of total deposits and total loans and advances were negatively and statistically Functional correlation between bank assets... http://www.ae.ef.unibl.org/ significant to the Deposit Insurance Fund in the long run (Ebiaghan & Jeroh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the growth of deposits onto the Deposit Insurance System's funds and its pay out capacity are as follows -the payout capacity is always larger at lower covered deposits' annual growth rate. Authorities should take into account the growth of deposits' impact when deciding on an annual premium level, especially if the country experienced a significant growth of deposits (Ognjenović, 2017, p. 123) Empirical research conducted in order to assess the relationship between the Deposit Insurance Fund and total deposits and loans showed that the volume of total deposits and total loans and advances were negatively and statistically Functional correlation between bank assets... http://www.ae.ef.unibl.org/ significant to the Deposit Insurance Fund in the long run (Ebiaghan & Jeroh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A decade after the recapitalization exercise with Nigeria Deposit Insurance Corporation (NDIC) a number of banks have been downgraded, some weaker ones have been forced to merge with strong ones whereas in other instances, some ailing ones have been acquired by other financial institution. As much as this is a concern to stakeholders and the general public especially regarding the safety of their deposits (Ebiaghan& Jeroh, 2020), keeping afloat the industry remains a challenge to bank operators. To survive the odds and to remain profitable in the banking business, bank institutions must maintain a certain degree of organizational effectiveness in all ramifications.…”
Section: Introductionmentioning
confidence: 99%
“…Earnings management is primarily accomplished through accounting transactions that are designed to achieve desired earnings level. Prior research suggests that managers have both personal and business motivations to display impressive or at the very least satisfactory performance in their reports on a consistent basis ( Ebiaghan, Ojugbeli & Okoye 2017;Ebiaghan & Esekhile 2018;DeFond and Park, 1997;Greenfield, Carolyn, Norman, and Wier 2008). However, due to a variety of reason, the sustainability of such a performance is sometimes impossible.…”
mentioning
confidence: 99%